STE(A)M: Not only education but also a lifestyle - Sachpatzidis Avraam; Fragulis George F.; Antoniadis Ioannis (SHS Web of Conferences, 2022)
If science can define meanings and measure results, art can express them and give a step forward to refreshment and innovation. The artist-scientist archetype started from Archimedes going to Nikolai Tesla, in about the inventor, the seeker, the dreamer, and the thinker, both as new scientist and artist. A growing number of schools are incorporating teaching methods that are more aligned to STEAM education (Science, Technology, Engineering, Arts and Mathematics) since it has become, almost very clear and concrete, that art’s education makes learning more fun and keeps everyone involved even more engaged. As exploring new possibilities, to lead innovation in the classroom and promote leadership at all levels, encourage teachers and principals, make the school and the whole system a dynamic one. The core value is that the need for STEAM education is critical, especially because there will be related jobs ready to be filled as soon as possible. This job is about to show, when and how can a STEAM educational concept can be delivered in a system that seems to have been destroyed from its old mistakes and can give a real boost to a new oriented public school, in the best possible integrated educational system for preparing students for the university and beyond. Primary inquiry, dialogue, and critical thinking seem to lead the way for a better life in the school environment and real-life society.